UJI KETAHANAN BEBERAPA VARIETAS JAGUNG (Zea mays L.) TERHADAP PENYAKIT KARAT DAUN (Puccinia polysora Underw.) DI DATARAN RENDAH - Denny Irawan; Hasanuddin Hasanuddin; Lahmuddin Lubis (Jurnal Agroekoteknologi, 2013)
Test of resistance of some varieties of corn (Zea mays L.) on leaf rust (Puccinia polysora Underw.)on lowland. The aim of the research was to know the resistance of some varieties of corn (Z. mays)on the leaf rust (P. polysora) on lowland. The research was conducted at Tanjung Selamat village,Medan. The research used cluster random design with ten treatments and three repetitions. Theresults of the research showed that the varieties of resistance were found in the varieties of Pioneer12, Bisi 12, Bisi 12, SHS 2. SHS 12, and DK 3. Tolerant varieties were found in the varieties ofPioneer 23, BISI 2, NK 22, and NK 99. The highest production was found in BISI 12 (6.51 tons/ha)and the lowest production was found in Pioneer 23 (4.02 tons/ha).Keywords : varieties of corn, Puccinia polysora Underw., leaf rust, varieties of resistance